Development of Beta-NMR Detection Electronics for VITO Beamline at ISOLDE Facility at CERN - Havránek, Daniel; Pešek, Michael; Paulitsch, Daniel; Kowalska, Magdalena; Bissel, Mark Lloyd; Král, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
Beta detected NMR (Nuclear Magnetic Resonance) is a method to determine the magnetic moments of short-lived isotopes with very high precision using beta particles emitted when the isotopes decay. This paper focuses on designing electronics for a beta particle detector to be used at the beta-NMR beamline VITO at ISOLDE facility at CERN. In the detector beta particles lead to the creation of eV photons which are detected with use of SiPMs (Silicon PhotoMultipliers). Key aspects of the design are linearity, vacuum compatibility, magnetic field compatibility and small size, due to space constraints.
Keywords: beta-particle detection; Beta-detected-NMR; SiPM; PCB; AD8001; AFBR-S4N66P024M; CERN; ISOLDE; VITO